The Use of Taboo Words in The Film “Dirty Grandpa” - Dwi Indrayasa, Kadek (Humanis, 2018)
Taboo words are cultural or religious custom that is not allowed to be used to someone else. However, taboo words are also found in daily conversation. Therefore, the aim of this study is to analyze the types, function and meaning of taboo words found in the film. The data of this analysis were taken from a film entitled “Dirty Grandpa”.  The data were collected through documentation method and note-taking technique. The data were descriptively analyzed based on the types, function and meaning of taboo words. The result of this analysis shows 10 (ten) types of taboo words in the film, namely Epithets, Profanity, Blasphemy, Obscenity, Cursing, Taboo, Vulgarity, Slang, Insult and slur, Scatology.  6 (six) function of taboo words were found; they are Create Attention, Discredit, Provoke Violent Confrontation, Endearment, The Creation of Strong Interpersonal Identification and Provide Catharsis and only three meanings were found, namely affective meaning, social meaning and connotative meaning.